Stoneware Pieces from Klaipėda Dating to 14th–18th Centuries - Ziabreva, Viktorija (Archaeologia Lituana, 2017)
In the early ages of the town of Klaipėda, stoneware production came from either the German production centers of Siegburg, Lower Saxony, Langerwehe, Waldenburg, Aachen/Raeren, Cologne, Frechen, Westerwald, Altenburg, Annaberg or from the centers located in England, London: Woolwich, Fullham and Lambeth factories and from the Nottingham production center. Earliest stoneware pieces, dated from the second half of the 13th c. to early 16th c., were distributed among the Castle and the early colonists’ town areas. The growth of this kind of vessels in the town coincides with the historical data on urban construction. Four functional groups of stoneware were identified in the studied material from Klaipėda. According to the stoneware data, it was possible to clarify the dating of some stoneware vessels and cultural layers in the Town area of Klaipėda. Keywords: stoneware ceramics, import, the clarification of the cultural layers, the Middle Ages, Klaipėda.